Hesitancy toward vaccination against COVID-19: A scoping review of prevalence and associated factors in the Arab world - Zufishan Alam; Salma Mohamed; Javaid Nauman; Rami H. Al-Rifai; Luai A. Ahmed; Iffat Elbarazi (Taylor & Francis Group, 2023)
Despite widespread availability of vaccines against SARS-CoV-2 virus, the cause of Coronavirus Disease 2019 (COVID-19), its uptake in many Arab countries is relatively low. This literature review aimed to scope evidence on COVID-19 vaccine hesitancy (VH) in the Arab world. A total of 134 articles reporting prevalence of COVID-19 VH and associated factors, conducted in any of the 22 Arab League countries, were reviewed. COVID-19 VH prevalence ranged from 5.4% to 83.0%. Female gender, young age, low education level and lack of previous influenza vaccine uptake were most commonly reported to be associated with COVID-19 VH. The most-reported personal concerns contributing toward VH were related to the rapid development, safety and side effects of vaccine, as well as an overall lack of trust in government policies toward pandemic control and widespread conspiracy theories. Tailored interventions to enable the distribution of trusted information and enhance public acceptance of immunization are warranted.